Efeitos da aplicação de tortas de pinhão manso e mamona no crescimento de feijão caupi e nas propriedades químicas e biológicas de um solo degradado de Irauçuba-CE. - Cunha Filha, Luiza Souza da (2011)
The residue resulting from the oil extraction of jatropha and castor seeds is considered an excellent source of organic matter, which is rich in nitrogen, phosphorus, potassium and other nutrients. However, the problem is concerned to the fate given to this seed residue, as generated in large scale, since the improper disposal of it may limit the efficiency of production and the environment conservation. In this sense, it was set a research with the objective to evaluate the effects of the application of these seed residues in the soil collected from two areas: an overgrazing site and other conserved as exclusion site, both located in Irauçuba county of Ceara State, Brazil. The study focused especially on chemical and biological parameters which are related to the soil quality. The experiment was conducted under greenhouse conditions belonging to the Department of Soil Science, Federal University of Ceará, Campus do Pici, Fortaleza-CE. Plant and soil were analyzed considering each site that received the seed residue. The experimental design was a completely randomized blocks in a 2 x 3 factorial (two areas and three doses of pie), with six treatments and four replicates, totalizing 24 experimental units for each seed residue; each unit consisted of a pot containing two plants. After 45 days of the seed residue application, the pots were sown with cowpea [Vigna unguiculata (L.)] and, after a 30 days growing period, it was determined the pH of the soil solution, the soil and plant NPK contents, Total Organic Carbon (TOC), density of spores in the soil microbial biomass carbon (MBC), soil basal respiration (SBR) and both metabolic (qCO2) and microbial (qMIC) quotients. The results showed that the overgrazing of the area (area 1) was favored by the application of the castor bean and jatropha seed residues, especially at the rate of 5% (D2) which had the highest values of qCO2, while the exclusion area (área 2) showed the highest values of soil MBC. The addition of jatropha and castor seed residues, at both rates, reduced the density of spores of the soil in both areas, but increased the TOC and NPK soil and plants contents, indicating that the application of these seed residues can be an alternative for rehabilitating degraded soil areas.